Implementasi Delapan Prinsip The-C Wheel Pada Pembelajaran Bahasa Inggris Berbasis Modul Bahasa Arab di Madrasah Diniyah Takmiliyah Al-Khoeriyyah - Tri Agustini Solihati Solihati (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program was initiated to respond to the needs of Madrasah Diniyah Takmiliyah Al-Khoeriyyah in Desa Linggaraja, a 3T (underdeveloped, frontier, and outermost) area where access to quality English education is limited. The main issue faced by the partner was the absence of English instruction due to curriculum constraints and a lack of qualified teachers. Parents expressed concern over their children's struggles with English at the secondary level. To address this, the program aimed to develop an English learning module integrated with the existing Arabic curriculum by implementing the eight principles of The-C Wheel: context, connection, coherence, challenge, curiosity, care, community, and creativity. The methods included institutional analysis, module development based on daily-used Arabic materials, teacher assistance using Google Translate, classroom teaching by the service team, and guided teaching simulations. Results indicated improved teacher engagement, increased student enthusiasm, and the successful creation of a copyrighted English module. In conclusion, the program effectively enhanced English instruction in a religious-based educational setting and is expected to serve as a replicable model for similar institutions in rural areas.